Pengaruh Sistem Pengendalian Manajemen terhadap Kinerja Karyawan - Audi Elshinta Gading; Adek Wahyuni Safitri; Mutiara Ramadani; Sebrina Handayani; Fitri Yani Panggabean (Universitas Muhammadiyah Surabaya, 2024)
This study aims to determine the effect of management control system on employee performance. Employee performance is an important aspect in achieving organizational goals. The method chosen uses quantitative, quantitative is a process for obtaining knowledge using numerical data as an analytical tool, data analysis techniques through the IBM SPSS statistical 23 program. t test research results, Management Control System (X) of 3.396, which is greater than the t table value of 1.98397, with a Significance value (Sig.) of 0.001 which is less than 0.05. Therefore, H0 is rejected and Ha is accepted, indicating that the Management Control System has a significant effect on Employee Performance. In this study, it was found that the calculated F value of 11.535> the F table value of 2.70 and the sig. value is 0.001 <0.05, so H0 is rejected and Ha is accepted, meaning that the Management Control System has a significant effect on Employee Performance. The management control system has a significant effect on employee performance. By providing structure, feedback, and motivation, this system can help employees reach their potential and contribute to the overall success of the organization.